PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN MUDHARABAH TERHADAP RETURN ON ASSET (ROA) PADA BANK UMUM SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN (OJK) - Besse Khadijah Irawan; Niluh Anik Sapitri (Jurnal Akuntansi dan Keuangan Syariah (Jurnal Akunsyah), 2022)
This study aimed (1) to determine the effect of the capital adequacy ratio on return on assets at Islamic Commercial Banks registered with Otoritas Jasa Keuangan (Financial Services Authority ((OJK), (2) to investigate the effect of mudharabah return on assets at Islamic Commercial Banks registered with OJK, and (3) to find out the effect of the capital adequacy ratio and mudharabah return on assets at Islamic Commercial Banks registered with OJK. This reserach was conducted from July to August 2021. The type of research conducted was quantitative descriptive with an associative approach. The data source used was secondary data. The population used covered all financil statements of Islamic Commercial Banks (ICB) in Indonesia registered with OJK  for the  2016-2020 period. The sampling technique used was the saturated sampling technique. The data was obtainedfrom times series of financial reports with a total of 60 samples. Observation and documentation were used as techniques in collecting data. The data analysis method used was multiple linear regression The results of this indicate that (1) partially, the capital adequacy ratio had a positive and significant effect on retun on assets at Islamic Commercial Banks (2) partially, mudharabah had no significant effect on return on assets at Islamic Commercial Banks, and (3) simulatneously, the capital adequacy ratio and mudharabah had a positive and significant effect on the return on assets of Islamic Commercial Banks. Based on the results of the research above, the capital adequacy ratio and  mudharabah have a substantial influence on return on assets at Islamic Commercial Banks registered with OJK. Therefore, the bank can supervise and maintain the quality of the capital adequacy ratio and mudharabah on ROA in increasing the profit of the bank. The implication shows that both variables of capital adequacy ratio and mudharabahhave a good influence on return on assets because they have a positive impact or can manage to increase bank profit.